Patellar tendon ultrasound in asymptomatic elite junior basketball players: A 12-month longitudinal study in 52 tendons - Cook, J. L.; Kiss, Z. S.; Khan, K. M.; Purdam, C. R.; Griffiths, L. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Patellar tendinosis has generally been considered a condition of those aged 20 years and over [1, 2] but a recent cross-sectional study suggests that it may occur as early as the early teenage years [3]. If US abnormalities predicted future clinical problems this would have important implications for prevention of jumper`s knee.